2023
DOI: 10.1038/s41598-023-33314-9
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence and effect of comorbidities and smoking status on severity and mortality of COVID-19 in association with age and gender: a systematic review, meta-analysis and meta-regression

Abstract: A COVID-19 patient often presents with multiple comorbidities and is associated with adverse outcomes. A comprehensive assessment of the prevalence of comorbidities in patients with COVID-19 is essential. This study aimed to assess the prevalence of comorbidities, severity and mortality with regard to geographic region, age, gender and smoking status in patients with COVID-19. A systematic review and multistage meta-analyses were reported using PRISMA guidelines. PubMed/MEDLINE, SCOPUS, Google Scholar and EMBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 210 publications
0
21
1
1
Order By: Relevance
“…These risk factors increase the risk of admission to intensive care units, and could be life-threatening [ 49 , 51 , 52 ]. In contrast to some studies, our study reported several comorbidities [ 47 , 52 54 ]. Interestingly, previous studies such as that of Ross Arena and his colleagues have indicated that unhealthy lifestyle behaviors, comorbidities, and COVID-19 syndemic in severe cases raise the question of a complex interaction of health factors, acting synergistically to worsen the overall consequences of the disease [ 4 6 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These risk factors increase the risk of admission to intensive care units, and could be life-threatening [ 49 , 51 , 52 ]. In contrast to some studies, our study reported several comorbidities [ 47 , 52 54 ]. Interestingly, previous studies such as that of Ross Arena and his colleagues have indicated that unhealthy lifestyle behaviors, comorbidities, and COVID-19 syndemic in severe cases raise the question of a complex interaction of health factors, acting synergistically to worsen the overall consequences of the disease [ 4 6 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The different risk factors reported in this meta-analysis are predictive of a severe and critical form of the disease, requiring patients’ admission to intensive care units (ICU). Our analysis has shown that the association between age, gender (male), obesity, and smoking status appeared with numerous comorbidities as risk factors for severe COVID-19 [ 47 , 48 ]. Indeed, several studies have reported that advanced age is associated with the severity of COVID-19, primarily due to physiological changes accompanying aging, a weakened immune system and underlying health issues [ 7 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding comorbidities, patients in the elderly group were more likely to have past medical history especially hypertension and diabetes which was a common finding in most studies dealing with the same topic ( 1 , 22 ).…”
Section: Discussionmentioning
confidence: 94%
“…In severe cases, the treatment options are still limited, and the emergence of new virus variants makes it even more difficult to develop new therapies. The occurrence of co-factors, including sex [3], age [4], and comorbidities [5], significantly affects the course of the disease and also influences the therapeutic response. Novel therapeutic approaches are therefore needed to better manage viral infections such as COVID- 19.…”
Section: Introductionmentioning
confidence: 99%